Presence Information System for Ciamis High School Informatics Teacher Based on a Microcontroller Using RFID: Sistem Informasi Presensi Guru SMA Informatika Ciamis Berbasis Mikrokontroler Menggunakan RFID - Bayu Pamungkas; Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2023)
Recording the teacher's attendance list is one of the important factors in the management of discipline. Information about teacher attendance can determine learning services and school progress at SMA Informatika Ciamis. Teacher attendance recording tools are needed based on observations made at the school, there are several problems and shortcomings from the attendance system which is usually done manually such as wasteful in the use of paper, time, and energy. Not only that manual attendance input can also experience errors and fraud in the hassle of making a teacher attendance recap and its management. The purpose of this research is to create a presence system using RFID (Radio Frequency Identification). This technology will later replace the role of paper and ink to record teacher attendance to make it easier for attendance officers to input practical data because they can retrieve and store attendance data from RFID tags directly, making it easier to report attendance to interested parties. And it can also reduce the use of a lot of presence paper, thereby reducing paper printing costs. This system uses the PHP programming language and the C database language used by MySQL.